Строптивая мишень: [повесть] / Татьяна Полякова - Полякова Татьяна (Авантюрный детектив, 2011)
Экземпляры: ф.7 (2012) / Инвентарный номер: 54469 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: П 54 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44